Comparison of caesarean section rate and maternal complications in elective induction versus spontaneous labor - Beigh, Salma Kousar; Mukhtar, Samar; Firdous, Nighat; Amaan, Fariha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Elective induction of labor is defined as an initiation of labor, either by mechanical or pharmacological means at a time earlier than nature regardless of a medical or obstetric indication. Objectives were to estimate the proportion of caesarean sections and vaginal deliveries and magnitude of maternal complications following elective induction and spontaneous labor. Methods: The study entitled “comparison of caesarean section rate and maternal complications in elective induction versus spontaneous labor in LD Hospital, Kashmir” was a hospital based observational study, conducted in the Postgraduate Department of Obstetrics and Gynaecology, LallaDed Hospital of Government Medical College, Srinagar over a period of one and a half years. Results: Women in induced labor group had slightly increased risk of caesarean section than those in spontaneous group. Fetal distress was the most common indication for caesarean section in both the groups. There was no difference in both groups regarding maternal complications such as perineal lacerations; postpartum hemorrhage (PPH); need for blood transfusions and post partum hospital stay. Conclusions: Though induction of labor is associated with a slight increased risk of caesarean delivery, it is not related to other maternal complications. Therefore inductions are safe in hands of safe obstetricians.